Skincare product recommendation system using Content-Based Filtering Technique (CBF) / Muhammad Fakhrullah Mohd Burhanudin - Mohd Burhanudin, Muhammad Fakhrullah (2024)
The Skincare Recommendation System aims to improve user experience and reduce the possibility of skin concerns resulting from incompatible selections by addressing frequent obstacles experienced by customers when choosing skincare products. The system evaluates product components and user-specific skin types by utilising the Content-Based Filtering Technique (CBF) which using TF-IDF and cosine similarity technique and provides customised suggestions based on common ingredient compositions. The project's goals are to research CBF, use this method to build a recommendation system, and assess the system's accuracy. The background study highlights the difficulties in choosing skincare products because of ignorance about the right components for various skin types.